Lithuanian museology: Development of Lithuanian Museology from the Latter Half of the 18th Century to the 21st Century - Kondratas, Ramūnas (Acta Museologica Lithuanica, 2017)
his is the first book to analyze and evaluate the development of Lithuanian museology (museum studies) from the latter half of the 18th century into the 21st century. It is based on the extensive research materials, many of them archival, gathered by the author Dr. Nastazija Keršytė during 2012–2014 while doing the research project “Development of Lithuanian Museology in 1752–2012”, sponsored by the Research Council of Lithuania (contract LIT-5-16). A stimulus for the writing of this monograph was the opportunity afforded by the government program Lithuanian Museums in 1812–2012 (Lietuvos muziejų kelias 1812–2012 m.), one of the initiatives undertaken in the Year of the Museum in 2012. Unfortunately, Dr. Keršytė died before completing this monograph on 18 May 2016, International Museum Day. As a long-time friend and colleague, I had promised to write an English-language summary of her book. More in PDF.